Occupational Stress Level in Agents and Supervisors of a Private Security Company Associated with Work-Related Factors - Lizardo Otero, Brunella Ysabel (2023)
This paper aims to determine the level of occupational stress associated with the work-related factors of agents and supervisors of a security company in Lima. A quantitative, non-experimental, correlational and cross-sectional approach was used. The sample consisted of 541 agents and supervisors of a private security company in Lima. A survey was used as the data collection technique. The results showed that work-related factors “incentives” (p < 0.001), “contract type” (p < 0.001), “/compensation” (p < 0.001) and “job stability” (p < 0.001) are related to occupational stress. Stress is related to various work-related factors such as incentives, contract type, compensation and job stability of security agents and supervisors of a private security company in Lima.